Acute neuromuscular responses to resistance training performed at different loads - Benson, C.; Docherty, D.; Brandenburg, J. (Journal of Science and Medicine in Sport, 2006)
The aim of this study was to compare the acute neuromuscular responses during resistance exercise performed with different loading protocols. Thirteen (N = 13) college-aged male subjects experienced in weight training completed two different weight training protocols involving a single elbow flexion exercise. During both protocols subjects performed three sets of the exercise with a 3-min rest between each set. One protocol required the subjects to perform each set to failure using 100% 10 repetition maximum (RM) load whereas the second protocol required the subjects to perform 10 repetitions for the first two sets using 90% 10 RM load and only go to failure on the third set. Maximal voluntary isometric contraction (MVIC), integrated EMG recording (iEMG) of the biceps brachii, and blood lactate were measured before and upon completion of the two training protocols. Subjects were able to perform a significantly greater volume of work (total repetitions × load) in the 90% 10 RM protocol compared to the 100% 10 RM protocol. Both protocols elicited similar cumulative levels of fatigue as reflected by a decrease in MVIC and iEMGmax and an increase in blood lactate (p = 0.05). As a result of the drop in repetitions performed in successive sets, it was concluded that training with 100% 10 RM while exercising to failure in each set may not optimise the training volume, which may have implications for chronic muscle adaptation.